2010
DOI: 10.21273/hortsci.45.12.1768
|View full text |Cite
|
Sign up to set email alerts
|

Spathe Color Variation in Anthurium andraeanum Hort. and Its Relationship to Vacuolar pH

Abstract: The relationship between vacuolar pH in Anthurium andraeanum (Hort.) and spathe color, cultivar, developmental stage, spathe location, spathe surface differences, and time after harvest was investigated with the overall long-term objective of developing a methodology for engineering blue-colored spathes. Chromospectral analysis of the pigmentation was also studied. Six experiments were conducted involving 23 cultivars of anthurium with each experiment arranged in a randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…found that the cell shape influenced the optical properties in Antirrhinum majus , the magenta epidermal cells were conical and the pink epidermal cells were flat. Avila-Rostant et al 38. speculated that there was correspondence between the lightness of the pigmentation and the vacuolar pH values with the lighter colours having higher pH values in anthurium ( Anthurium andraeanum Hort.).…”
Section: Discussionmentioning
confidence: 99%
“…found that the cell shape influenced the optical properties in Antirrhinum majus , the magenta epidermal cells were conical and the pink epidermal cells were flat. Avila-Rostant et al 38. speculated that there was correspondence between the lightness of the pigmentation and the vacuolar pH values with the lighter colours having higher pH values in anthurium ( Anthurium andraeanum Hort.).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly as previously shown in Petunia, a bHLH protein that regulated anthocyanin biosynthesis may also control vacuole acidification (Spelt et al 2002;Quattrocchio et al 2006). It is possible that the higher pH values observed in the white Plant Cell Tiss Organ Cult and green spathes could have been due to pleiotropic effects of controlling elements on anthocyanin biosynthesis (Avila-Rostant et al 2010). The authors proposed that for future transgenic production that the anthurium spathe pH should be taken into consideration in order to generate the desired novel colour with particular reference to the engineering of blue flowers which would require a high pH background for the development of blue hues (Katsumoto et al 2007).…”
Section: Manipulation Of Flower Colourmentioning
confidence: 86%
“…Factors such as cell shape, the presence of various metal ions, stacking of anthocyanins with copigments and vacuolar pH (Mol et al 1998;Andersen and Jordheim 2006;Grotewold 2006) can all alter the observed colour. Of these, only vacuolar pH has been studied in anthurium (Avila-Rostant et al 2010), where a relationship between spathe colours and pH was observed with green (colour group mean 5.74) and white (mean 5.57) spathes having the highest pH followed by corals (mean 5.38), pinks (mean 5.52), reds (mean 5.09) and oranges (mean 4.51). The differences between colour groups were shown to be significant apart from that between pinks and reds.…”
Section: Manipulation Of Flower Colourmentioning
confidence: 99%
“…CaCl 2 can effectively increase PAL activity and anthocyanin content in the pedicel (Avila-Rostant et al, 2010). It is proved that Ca 2+ can overcome the decrease in photosynthate (mainly sugars) accumulation and PAL activity caused by insufficient sunlight (Wang, 1999;Wang et al, 2018) and can provide sufficient precursors and pathways for the synthesis of anthocyanins, thereby increasing anthocyanin content (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%